Quality of life of dentists in manila An assessment - Liberato, Andrea Y.
It has been the layman's impression that the life dental practitioners lead is easy and comfortable. This study is an attempt to affirm this assumption. The subjects are practicing dentists in Manila. Questionnaires on the profile of the average working day of the subjects were distributed to 130 dentists who were randomly chosen from the list of dentists of the Manila Dental Society. Answers from the 67 filled questionnaires were then tallied and averaged using descriptive statistics. Results showed that 82% of dentists in Manila engage in at least 30 minutes of exercise at a time, 96% go out with friends, and 67% admit to have earned enough to support a comfortable lifestyle despite not having adequate time and energy for activities not related to their practice, better social lives, and the improvement of their spiritual status. Therefore, most Manila dentists lead good, healthy, and comfortable lives.